(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
In the agile world, the web application development has to be accurate and economical. One of the best ways to achieve the productivity is by reducing the complexity. The complexity can be reduced by the separation of concerns. If there is a reduction of concerns of the configurations and the boilerplate code. One approach is to use spring framework for development. It provides a decoupled way of developing web applications. Web application development becomes simple in spring with its various features. The underlying spring architecture and a case study using spring have been presented in the paper [1].